(untitled) (Papeles, 2025)
This text understands the development of state social intervention beginning in the 1930s as part of the process of institutionalizing and legitimizing social work as a professionalized form of care. It concurs in understanding the connection between these processes and the emergence of feminized professions, especially those associated with care and social health policies. The purpose of this article is to include the variable of the environment in health education and social prophylaxis, as a device for hygiene and social medicine, from a eugenic perspective. For this analysis, several texts published in the annals of the Argentine Association of Biotypology, Eugenics, and Social Medicine (AABEMS) will be considered. The concept of health education in relation to social service as part of health care, and the actions of social workers and visitors in this context, will be explored. This contribution aims to give visibility to the work of this profession, which contributed, among other things, to the configuration of the social and health fields.